Efektivitas Model Pembelajaran Kooperatif Tipe Jigsaw Berbantuan Tutor Sebaya Untuk Meningkatkan Hasil Belajar Mata Pelajaran Pendidikan Agama Hindu Dan Budi Pekerti Siswa SMK Kelas XI - Yogi Parwati, Ni Wayan (Metta : Jurnal Ilmu Multidisiplin, 2025)
The learning process for Hindu religion and character education subjects has so far tended to be monotonous and one-way so that student learning outcomes have not been optimal. This study aims to analyze the effect of using the Jigsaw cooperative learning model assisted by peer tutors on the learning outcomes of Hindu Religion and Character Education subjects of Grade XI Vocational High School Students. This study uses a one group pretest-posttest design. The study was conducted at SMK Negeri 7 Denpasar. The research sample was 19 students of grade XI Hospitality in the 2023/2024 academic year. The research instrument used a valid and reliable learning outcome test. Data were analyzed descriptively and using inferential analysis of the dependent sample T test. The results of the study stated that there was a significant difference in learning outcomes in grade XI Hospitality students before and after being taught with the Jigsaw cooperative learning model assisted by peer tutors. Thus, it can be concluded that the Jigsaw type cooperative learning model assisted by peer tutors is effective in improving learning outcomes in the subjects of Hindu Religion and Character Education.